Give them toys? Military allocations and regime stability in transitional democracies. Issue 7 (3rd October 2018) - Powell, Jonathan; Faulkner, Christopher; Dean, William; Romano, Kyle
ABSTRACT: In contrast to the conventional wisdom that democratization reduces coups, 46% of coups targeted democracies from 2000–2009, twice the rate seen in the prior half-century. Efforts to explain coups have arrived at wildly varied conclusions regarding the vulnerability of democracies. We argue that this is attributable to regime type acting as a conditional influence. We theorize that democratization incentivizes old elites to veto the process, and these vetoes are more likely to occur when the new regime cannot credibly commit to the military's corporate interests. Using cross-national data for 172 states for the years 1952–2009, we find that though young democracies are more vulnerable to coups than either civilian authoritarian regimes or older democracies, this vulnerability is mitigated when military expenditures are near or above the sample mean. We also find that commonly argued determinants of coups appear to be driven by their influence in democracies, suggesting the need for scholars to revisit commonly held assumptions regarding autocratic survival.